Acid induced duodenal ulcer pain: the influence of symptom status and the effect of an antispasmodic. Issue 2 (February 1989) - Kang, J Y; Yap, I; Guan, R; Tay, H H; Math, M V
Abstract : The aims of this study were to determine whether the development of acid induced duodenal ulcer pain was influenced by the symptomatic status of the patient and whether the administration of an antispasmodic could abolish pain. One hundred millilitres of 0.1 N hydrochloric acid was infused onto the ulcer craters or scars of 143 duodenal ulcer patients on 168 occasions. Symptomatic patients were randomised to receive 40 mg of hyoscine intravenously before acid infusion, or to a control group. Typical ulcer pain developed in seven of 55 (13%) instances for non-symptomatic patients, 24/57 (42%) of control symptomatic patients, and 20/56 (36%) of symptomatic patients given hyoscine. (Asymptomatic group v control symptomatic group, p less than 0.005; control symptomatic group v hyoscine group, NS - 95% confidence limits 12% in favour of the control and 24% in favour of the hyoscine group). The results suggest that acid infusion seldom reproduces ulcer pain in non-symptomatic duodenal ulcer patients and that the pathogenesis of acid induced duodenal ulcer pain probably involves a mechanism other than spasm, as pain was not prevented by an anticholinergic.